1995
DOI: 10.1002/cpp.5640020303
|View full text |Cite
|
Sign up to set email alerts
|

Another dodo bird verdict? revisiting the comparative effectiveness of professional and paraprofessional therapists

Abstract: We examine major criticisms of studies comparing paraprofessionals' and professionals' therapeutic effectiveness. Such analysis does not support the contention that methodological weaknesses of the studies produced systematic biases against professional therapists. Thus, despite common beliefs to the contrary, the finding that formal training does not predict successful therapy appears sound. We discuss the implications of this finding for research, training, and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Only two studies have found no signifi cant difference between self-help programs involving telephone contact and completely self-administered programs, or a wait list condition (Mead et al, 2005;. There is also considerable data indicating that paraprofessionals can be just as effective as professionals in providing viable therapy options (Boisvert & Faust, 2003;Christensen & Jacobson, 1994;Faust & Zlotnick, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Only two studies have found no signifi cant difference between self-help programs involving telephone contact and completely self-administered programs, or a wait list condition (Mead et al, 2005;. There is also considerable data indicating that paraprofessionals can be just as effective as professionals in providing viable therapy options (Boisvert & Faust, 2003;Christensen & Jacobson, 1994;Faust & Zlotnick, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…In building effective therapeutic relationships, personal attributes are often more important than technical skills learned in professional training. Faust and Zlotnick (1995) found that adequately supervised unqualified staff delivered psychological care as effectively as professionally trained staff. Humble practitioners might agree with Pashley’s (1992) observation that mental health practice relies on common sense as much as theoretical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…diagnosis) did not appear consistently better than inexperienced participants (e.g. Ebling & Levenson, 2003; see Garb, 1989, for a review and for critiques Berman & Norton, 1985;Durlak, 1979;Faust & Zlotnick, 1995;Strasser & Gruber, 2004). Although some research suggests training improves diagnosis (e.g.…”
mentioning
confidence: 96%